SOME THEORETICAL ISSUES ON RESOURCE MOBILIZATION MANAGEMENT FOR EARLY CHILDHOOD EDUCATION DEVELOPMENT IN THE CURRENT CONTEXT - Le Hoai Nam (Tạp chí Khoa học, 2025)
To implement the Education Development Strategy to 2030, with a vision to 2045, early childhood education requires substantial investment in human resources, infrastructure, and financial resources. In addition to funding from the state and local budgets, mobilizing extra-budgetary resources plays a crucial role in ensuring the sustainable development of early childhood education. This study analyzes the theoretical foundations of resource mobilization management for early childhood education, clarifying the key aspects of management through four stages: (1) Planning resource mobilization; (2) Organizing implementation; (3) Directing execution; and (4) Evaluating, providing feedback, and improving the mobilization process. The findings contribute to providing both scientific and practical bases for enhancing the efficiency of resource mobilization, thereby meeting the developmental demands of early childhood education in the current context.